2012
DOI: 10.1016/j.jand.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Is Associated with Obesity among US Adults in 12 States

Abstract: A redesigned food insecurity question that measured food stress was included in the 2009 Behavioral Risk Factor Surveillance System in the Social Context optional module. The objective of our study was to examine the association between food stress and obesity using this question as a surrogate for food insecurity. Our analytic sample included 66,553 adults from 12 states. Food insecurity was determined by response (always/usually/sometimes) to the question,"Howoften in the past 12 months would you say you wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
5
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(195 citation statements)
references
References 34 publications
9
174
5
7
Order By: Relevance
“…This finding is consistent with previous research that has found that individuals who were food insecure were more likely to be overweight or obese [47,71,72]. It should be noted that much Canadian research investigating food security/insecurity has used the food security module developed for the Canadian Community Health Survey (CCHS) which defines food security/insecurity somewhat differently than the present investigation [73].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous research that has found that individuals who were food insecure were more likely to be overweight or obese [47,71,72]. It should be noted that much Canadian research investigating food security/insecurity has used the food security module developed for the Canadian Community Health Survey (CCHS) which defines food security/insecurity somewhat differently than the present investigation [73].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies found that BMI and/or BMI changes are often linked to gender, age, race/ethnicity, education, and income [12,33,[42][43][44][45]. In addition, food insecurity, place of residence, and lifestyle factors, such as physical activity, smoking, and alcohol use, are all potentially associated with body mass or body mass change [44,[46][47][48][49][50][51]. Covariates can be classified as risk factors (time-invariant) and time-varying covariates.…”
Section: 2mentioning
confidence: 99%
“…Because food insecurity implies a lack of access to food, it is most often associated with malnutrition and weight loss. However, research also indicates that reliance on low-quality, energyrich foods can result in overweight or obesity [28], particularly when combined with other socioeconomic or geographic obstacles prevalent in food-insecure areas. For example, people living in these areas often have limited agency over their environments and face barriers to safe outdoor physical activity and the opportunity to purchase and prepare healthful foods [29].…”
Section: Food Securitymentioning
confidence: 99%
“…Many of these focus on at-risk groups such as children, pregnant women, and older adults and revolve around foodborne illness and food safety; measures of food security; environmental issues such as climate change and genetically modified crops; and national and global food aid policies. The concept of food security benefits from the diverse and experimental nature of the literature, particularly given the associations between food insecurity, health status indicators such as obesity and malnutrition, and special interest groups such as immigrants, school children, and mothers [20,28,33].…”
Section: Food Securitymentioning
confidence: 99%
“…There is a need, however, for participatory research that works with residents of food deserts to explore how they understand and respond to their local foodscape and that builds the community's capacity to transform the local food environment. A large number of studies have looked at the effects of food insecurity on the health outcomes of overweight and obesity (Brown et al, 2007;Dinour, Bergen, & Yeh, 2007;Pan, Sherry, Njai, & Blanck, 2012). We question if the particular issue of obesity is a priority to many of the communities experiencing food insecurity.…”
Section: Revitalizing Food Insecurity Researchmentioning
confidence: 99%